Qualidade da carcaça e carne de novilhos alimentados com dietas com borra de soja - Segabinazzi, Luciane Rumpel (2012)
The objective of this study was to evaluate carcass characteristics, the non carcass components, the lipid profile and the sensorial characteristics of meat from steers finished in feedlot fed diets containing different levels of inclusion of soybean soapstock. We used 30 Nellore and Charolais-Nellore crossbred steers with initial mean age of 20 months and initial mean weight of 20 months and 328.3 kg (±18.8 kg) were allotted to five dietary treatments: 0, 30, 60, 90 and 120 g of soybean soapstock/kg dry matter (DM) of diet . The diet consisted of forage(corn silage):concentrate ratio of 39:61 (DM basis), and was offered "ad libitum" during 84 days. A inclusão de até 120 g de borra de soja/kg de MS na dieta não alterou o peso de abate e os rendimentos de carcaça quente e fria, assim como os componentes teciduais músculo, gordura e osso. The inclusion up to 120 g of soybean soapstock/kg DM in the diet did not alter the slaughter weight and hot and cold carcass yields, as well as the muscle, fat and bone tissues. It also did not alter the empty body weight and yield, and hot and cold carcass yields adjusted for the empty body weight. The relative weight of the blood decreased with the addition of up to 55 g of soybean soapstock/kg DM in the diet, but the inclusion of up to 120g/kg DM in the diet promoted a linear increase in the relative weight of the lung and spleen, a linear reduction of the relative weight of the omasum and rumen fat. The kidney fat deposition, when adjusted for empty body weight, increased with the inclusion of up to 50 g of soybean soapstock/kg DM. The total weight of external components, vital, gastrointestinal and internal fat did not differ. With respect to meat quality, including between 83 to 91 g soybean soapstock/kg of diet DM promoted the highest levels of Vacenic (C18: 1 trans -11) and CLA (C18: 2 cis-9 trans-11) fatty acids, however, promoted also the highest levels of trans fats in the steers meat. The levels of fatty acids of the omega-3 group decreased linearly with the inclusion of dietary soybean soapstock , increasing the omega-6:omega-3 ratio in the steers meat. The lipid content increased linearly with the addition of soybean soapstock , but the content of cholesterol remained similar. The inclusion of dietary soybean soapstock did not affect meat marbling, color, palatability, juiciness, tenderness, and losses of the thawing and cooking liquid.